Suicidal Behavior and Psychological Distress in University Students: A 12-nation Study. Issue 3 (2nd July 2016) - Eskin, Mehmet; Sun, Jian-Min; Abuidhail, Jamila; Yoshimasu, Kouichi; Kujan, Omar; Janghorbani, Mohsen; Flood, Chris; Carta, Mauro Giovanni; Tran, Ulrich S.; Mechri, Anwar; Hamdan, Motasem; Poyrazli, Senel; et al.
Abstract : This study investigated the prevalence of suicidal behavior and psychological distress in university students across 12 nations. A total of 5, 572 university students from 12 countries were surveyed about suicide ideation, suicide attempts, and psychological distress by means of a self-administered questionnaire. Almost 29% of the samples reported having contemplated suicide and 7% reported attempting suicide. Of the total sample, 51.1% scored above the General Health Questionnaire-12 ≥ 3 cut-off points, 41.6% above the GHQ-12 ≥ 4 cut-off points, and 33.8% scored above the GHQ-12 ≥ 5 cut-off points. While odds of suicide ideation were elevated in Austria and the UK, reduced ORs were detected for China, Italy, Saudi Arabia, Tunisia, and Turkey. Similarly, while odds of suicide attempt were high in Jordan, Palestine, Saudi Arabia, and to some extent in Turkey, reduced ORs were observed for Austria, China, Italy, Japan and the United States. Elevated ORs for psychological distress were seen in Japan, Jordan, Palestine, Saudi Arabia, Tunisia, and Turkey but reduced ORs were noted in Austria, China, Iran, Italy, and the United States. Psychological distress was strongly associated with reports of suicide ideation and attempts. Suicide ideation, suicide attempt, and psychological distress are common in university students but their rates vary depending on the sociocultural context. Due attention should be devoted to the mental health needs of young adults enrolled in higher educational institutions and more cross-cultural research is warranted to better understand the etiology of the observed intersocietal variations in suicidal behavior and psychological distress.